ANALISIS MOTIVASI BERPRESTASI MAHASISWA PGSD UNIVERSITAS NUSANTARA PGRI KEDIRI TINGKAT II PADA MATA KULIAH PENGEMBANGAN BAHAN AJAR - Karimatus Saidah; Rima Trianingsih (PEDAGOGIK : JURNAL PENDIDIKAN, 2018)
Motivation of achievement is the interest to achieve success in academics. Motivation of achievement demonstrated by efforts and seriousness in following each lecture and exercise the tasks. Mc Lelland suggests there are six characteristics of individuals who have the motivation high achievers among these: strong feelings for mecapai purpose, responsibility, take risks, are evaluative, creative and innovative, and like a challenge. To find out motivation of achievement in course learning materials development, then it needs to be done a study. This research used the qualitative approach. The model used in this study was a case study. Data analysis used qualitative descriptive analysis. The results of the interview and observation during course  learning materials development support the motivational characteristics of achievers. This means, in general student PGSD level II has motivated achievers in course learning materials development.